Case Report: Acute kidney injury due to minimal dilated obstructive nephropathy in the context of gastric cancer - Xiang, Xinyu; Wei, Xiaobao; Miao, Jiayi; Sun, Meng; Cao, Wei; Zhao, Baiqiao; Zhang, Yiwen; Wei, Juanyu; Zhu, Lin; Zhang, Yongping; Zhang, Ting; Zhang, Liyuan (Frontiers in Oncology, 2025)
Postrenal obstruction is a rare but reversible cause of acute kidney injury (AKI), often underrecognized when hydronephrosis is mild or absent. We present a 55-year-old woman with gastric cancer who developed severe AKI requiring hemodialysis. Initial non-contrast abdominal CT revealed only mild bilateral hydronephrosis without obvious ureteral obstruction. Given these subtle radiologic findings and a history of chemotherapy and NSAID exposure. Initially, a multidisciplinary team attributed the AKI to intrinsic renal causes. Subsequent renal biopsy revealed only minimal glomerular changes, insufficient to explain the degree of renal dysfunction. Despite supportive care, her renal function continued to decline. Further urological evaluation led to the placement of bilateral ureteral stents, which resulted in a prompt increase in urine output and improvement in serum creatinine. However, rapid restenosis occurred within four days, necessitating percutaneous nephrostomy. This two-step intervention restored renal function and improved short-term prognosis. This case underscores the diagnostic challenge of postrenal AKI in malignancy, particularly when imaging findings are subtle. Peritoneal carcinomatosis may cause ureteral encasement through mechanisms such as inflammation, fibrosis, and lymphatic disruption, often without significant collecting system dilation. Timely urologic intervention, guided by clinical judgment and supported by multidisciplinary collaboration, is critical to improving outcomes in such atypical presentations.